The Influence of the Endogenous and Exogenous Factors on Credit Institutions’ Return on Equity - Balteș, Nicolae; Rodean (Cozma), Maria Daciana (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
The research’s purpose is to study the credit institutions’ performance, from the shareholders’ point of view, through return on equity (ROE). It aims to identify a dependency relationship between return on equity (ROE) and endogenous factors (the growth rate of credit portfolio, the growth rate provisions, the solvency ratio), on the one hand and, on the other hand between ROE and the exogenous ones (GDP and inflation rate). The research was done over an horizon of 10 years (2004-2013) on the evolution of the return on equity indicator of two credit institutions listed on Bucharest Stock Exchange (Carpathian Commercial Bank SA and Banca Transilvania SA), highlights their vulnerability to economic conditions. The results obtained indicates, that in both credit institutions, the variation of return on capital is determined in a significant proportion by intern factors and it is conditioned in a insignificant share by the exogenous factors.